2017
DOI: 10.5152/turkpediatriars.2017.3989
|View full text |Cite
|
Sign up to set email alerts
|

Etiological evaluation of primary congenital hypothyroidism cases

Abstract: Aim: Primary congenital hypothyroidism is frequently seen endocrine disorder and one of the preventable cause of mental retardation. Aim of study was to evaluate the frequency of permanent/transient hypothyrodism, and to detect underlying reason to identfy any marker which carries potential to discriminate permanent/transient form. Material and Methods:Forty eight cases older than 3 years of age, diagnosed as primary congenital hypothyroidism and started thyroxin therapy in newborn-period, and followed up betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 21 publications
4
11
0
10
Order By: Relevance
“…In many studies, it has been reported that CH is more common in girls (13,14). However, in recent studies, male dominance has been reported, similar to our study (15)(16)(17). Since dysgenesis is known to be more frequent in girls and the rate of dysgenesis is relatively low in our study, it was thought that the higher frequency of males could be related to reasons other than dysgenesis.…”
Section: Discussionsupporting
confidence: 81%
“…In many studies, it has been reported that CH is more common in girls (13,14). However, in recent studies, male dominance has been reported, similar to our study (15)(16)(17). Since dysgenesis is known to be more frequent in girls and the rate of dysgenesis is relatively low in our study, it was thought that the higher frequency of males could be related to reasons other than dysgenesis.…”
Section: Discussionsupporting
confidence: 81%
“…Özgelen et al (13) reported that the rate of dysgenesis was found to be 83.7% of the patients with CH (51.7% hypoplasia, 21.7% agenesis, 10.3% ectopia) and rate of dyshormonogenesis was found to be 10.3% in patients; etiological distribution in this study was made only among the cases with permanent CH and both USG and scintigraphy were used for etiological evaluation. Similarly, in the study of Bezen et al (19), etiological distribution was evaluated among the cases with permanent CH; rate of dysgenesis was found to be 52.2% (34.8% hypoplasia, 17.4% ectopia) and rate of dyshormonogenesis was found to be 47.8% in patients. Although there are many studies which have reported that the rate of dysgenesis is high (20,21), there has been an increase in the rate of dyshormonegenesis in recent studies in accord with our findings (19,22).…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, in the study of Bezen et al (19), etiological distribution was evaluated among the cases with permanent CH; rate of dysgenesis was found to be 52.2% (34.8% hypoplasia, 17.4% ectopia) and rate of dyshormonogenesis was found to be 47.8% in patients. Although there are many studies which have reported that the rate of dysgenesis is high (20,21), there has been an increase in the rate of dyshormonegenesis in recent studies in accord with our findings (19,22). An Italian national study conducted by Olivieri et al (12) reported the rate of dysgenesis in CH cases was 82% between years 1987 and 1998 although it decreased significantly compared to the previous period with a rate of 58% between years 1999 and 2006 due to significant chnages in the screening protocols used in Italy and, the authors speculate, the increased survival of many more premature infants.…”
Section: Discussionmentioning
confidence: 90%
“…1,33 Using iodine solvents in neonatal navel care and post-surgery operation care in mothers are still ongoing in both cesarean and normal delivery. 40 Some recent reports indicate iodine deficiency in parts of Iran. 41 A national study also demonstrated iodine deficiency in pregnant women, despite sufficiency in the iodine status of the total population.…”
Section: Discussionmentioning
confidence: 99%